Combination Strategies to Optimize Efficacy of Dendritic Cell-Based Immunotherapy - van Gulijk, Mandy; Dammeijer, Floris; Aerts, Joachim G. J. V.; Vroman, Heleen (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are antigen-presenting cells (APCs) that are essential for the activation of immune responses. In various malignancies, these immunostimulatory properties are exploited by DC-therapy, aiming at the induction of effective anti-tumor immunity by vaccination with ex vivo antigen-loaded DCs. Depending on the type of DC-therapy used, long-term clinical efficacy upon DC-therapy remains restricted to a proportion of patients, likely due to lack of immunogenicity of tumor cells, presence of a stromal compartment, and the suppressive tumor microenvironment (TME) leading to the development of resistance. The efficacy of different types of DC-therapy is dependent on the type of DC used and which type of antigen is used. In order to circumvent tumor-induced suppressive mechanisms and unleash the full potential of DC-therapy, considerable efforts have been made to combine DC-therapy with chemotherapy, radiotherapy or with immunomodulatory therapeutics, such as checkpoint inhibitors. These combination strategies could enhance tumor immunogenicity, stimulate endogenous DCs following immunogenic cell death, improve infiltration of cytotoxic T lymphocytes (CTLs) or specifically deplete immunosuppressive cells in the TME, such as regulatory T-cells and myeloid-derived suppressor cells. In this review, different strategies of combining DC-therapy with immunomodulatory treatments will be discussed. These strategies and insights will improve and guide DC-based combination immunotherapies with the aim of further improving patient prognosis and care.